Patterns and Short Term Outcome of Children with Major Congenital Anterior Abdominal Wall Defects Admitted At Mbarara Regional Referral Hospital, South Western Uganda, from September 2019 to June 2020. - Mohamed, Jamal Abade; Migisha, Richard; Oyania, Felix; Wesonga, Ann Shikanda; Mohamed, Ahmed Abade; Situma, Martin (American Journal of Health, Medicine and Nursing Practice, 2022)
Background: Omphalocele and gastroschisis are the most common major congenital abdominal wall defects (CAWDs) globally. Mortality among neonates major CAWDs is higher in low-income countries than in high-income countries. This study described the patterns and short-term clinical outcomes of infants with gastroschisis and omphalocele at a regional referral hospital in southwestern Uganda. Methods: A case series was conducted at Mbarara Regional Referral Hospital ten months. Children born with CAWD during the study period 54 samples size were consecutively recruited into the study. Data were entered, cleaned, and analyzed using Stata version 15. Descriptive statistics were performed where continuous variables were summarized using median and interquartile ranges, while categorical variables were summarized using frequencies and proportions. Time to mortality was assessed using Kaplan–Meier survival analysis. Results: A total of 54 newborns were recruited into the study, of which 40 (70.04%) had Gastroschisis and 14(25.93%) had omphalocele. The median age of the infants was 9 days with an interquartile range of 4 to 21days. Of the 54 newborns, 30(69.2%) were male within the age group of 1-10 days. Mortality was higher in babies with complex gastroschisis (22) than simple gastroschisis (10). Not administering antibiotics and low birth weight were the factors associated with mortality among infants diagnosed with gastroschisis and omphalocele in the neonatal period. Conclusion: The most common observed defect was gastroschisis, Mortality was generally high among children presenting with gastroschisis. Complex gastroschisis has a poorer prognosis than simple gastroschisis over 30 days follow up period. Non-use of antibiotics before referral to a health facility and low birth weight were the factors associated with mortality among infants diagnosed with gastroschisis and omphalocele in the neonatal period. Recommendation: The most common pattern observed was Gastroschisis. The majority of children presenting with Omphalocele were more likely to survive for 30 days. There is a need for timely referral for babies born with congenital anterior abdominal wall defects
Keywords: Congenital abdominal wall defect; Omphalocele; Gastroschisis; Mortality; Uganda